2001
DOI: 10.1021/es001431k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis oftert-Butyl Methyl Ether (MTBE) in Dilute Aqueous Acid

Abstract: tert-Butyl methyl ether (MTBE) is generally considered to be resistant to chemical transformation in aqueous solution. This lack of reactivity has led to concerns of the long-term impacts of MTBE in groundwater. Although hydrolysis in the presence of strong acids has been recognized as a mechanism for MTBE transformation, it has been discounted as a significant reaction under environmental conditions. In this study, we have examined the fate of MTBE and other ether oxygenates under moderately acidic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 42 publications
4
33
0
Order By: Relevance
“…As the monooxygenase involved in the degradation of acetone was clearly different (Table 4), acetone should not compete with MTBE and TBA. The degradation of TBF formed after oxidation of MTBE was previously shown to be a spontaneous hydrolysis at acidic pH (O'Reilly et al, 2001). No data were available on the fate of TBF at neutral pH.…”
Section: Limiting Factors At the First Oxidationmentioning
confidence: 99%
“…As the monooxygenase involved in the degradation of acetone was clearly different (Table 4), acetone should not compete with MTBE and TBA. The degradation of TBF formed after oxidation of MTBE was previously shown to be a spontaneous hydrolysis at acidic pH (O'Reilly et al, 2001). No data were available on the fate of TBF at neutral pH.…”
Section: Limiting Factors At the First Oxidationmentioning
confidence: 99%
“…Although initial studies suggested that MTBE was not subject to extensive biodegradation under anaerobic conditions (35,53), it is now known to be degraded, albeit slowly, under methanogenic (51), sulfate-reducing (43), iron-reducing (13), and nitrate-reducing (5) conditions. Little is presently known about the pathway of MTBE biodegradation under any of these conditions, although it has been suggested that the anaerobic biodegradation could be initiated by a hydrolytic mechanism (39). Like many other gasoline components, the rate of MTBE degradation is higher under aerobic than anaerobic conditions.…”
mentioning
confidence: 99%
“…27 But several authors 31,32 reported the possibility of TBA production by acid hydrolysis of MTBE during heated headspace analysis of acidified samples giving pH of between 1 and 2, and pH of sample is changed to 3 in this study. The stability of each target compound along time was studied by calculating the percentage of recoveries of spiked soil samples after 1, 2, 3 and 4 weeks.…”
Section: Resultsmentioning
confidence: 70%